Evaluation of the bacterial agents associated with PID among women of reproductive age at Kampala International University Teaching Hospital - Baruti, Petrus; Nzabandora, Emmanuel; Agwu, Ezera (Biotechnology and Allied Fields, 2022)
Pelvic inflammatory disease (PID) is major health problem in developed and developing country involving more young women. It is associated with high rate of female reproductive health morbidity; it can complicate with ectopic pregnancy, infertility and chronic pelvic pain. A poor response therapy increases the likelihood of these complications; this could be due to an increase in antimicrobial resistant pathogens. The aim of this research was to determine common bacterial pathogens from endocervical swab of women with PID at Kampala International University Teaching Hospital. This was a cross-sectional study conducted among women who attended gynecology clinic at Kampala International University Teaching Hospital. Consecutive enrolment of 324 participants who consented to participate was done daily until a required sample size was realized from November 2019 to January 2020. Structured questionnaires were used to collect data on associated factors; endocervical swab was taken from patient clinically diagnosed with PID. Culturing for colony characteristics followed by Gram stain was used for provisional identity of pathogenic bacteria. Further identification was done by a set of biochemical tests. Data was analyzed using STATA VERSION 14.2. Not being educated, having two or more sexual partners, previous history of PID and induced abortion, also the previous use of contraceptives specifically the use of IUD ,were all significantly associated with Pelvic inflammatory disease (P value <0.05). The isolated bacteria was Staphylococcus aureus and the least-prevalent pathogen was citrobacter species. In conclusion, Staphylococcus aureus is the commonest organism isolated from the endocervical swab of patients with PID. Keywords: Bacteriology, Pelvic, Inflammatory, Disease and Women
Keywords: reproductive age; bacterial agents; PID among women